Design and Implementation of virtual simulation experiment platform for computer specialized courses. (December 2020) - Song, Guanghui; Nie, Yan; Chen, Genlang; Tong, Youcheng
Abstract: For the practical teaching of computer specialized courses in colleges and universities, this study proposes the construction method of virtual simulation experiment platform based on OpenStack, Docker, Seafile and Raspberry Pi, and on this basis, deeply discuss the design and implementation details of the course experiment. The construction and application of virtual simulation experiment platform change the traditional teaching method fundamentally, reduce the cost of laboratory construction and management, which have important reference value to realize the remote experiment teaching. The virtual simulation experiment platform is composed of four parts: virtual machine, application container, cloud storage and client, which can meet the daily teaching needs, cultivate students' interest in learning, and improve their innovation ability.